To Rise Again At A Decent Hour : A Novel - Ferris, Joshua, (LITTLE, BROWN AND COMPANY, 2014)
After noticing his identity has been stolen and used to create various social media accounts, a man with a troubled past, Paul O'Rourke, begins to wonder if his virtual alter ego is actually a better version of himself.